Fuzzy intrusion detection system for MANET packet dropping attack - Tingting LU; Xu HAN (Dianxin kexue)
For further detecting the packet dropping attack action, a fuzzy intrusion abnormity-based detection system（FIADS）was proposed. Based on Sugeno-type fuzzy inference system, FIADS detected the attack actions of each node by a distributed manner, and then moved these malicious nodes out of MANET to improve the frequency spectrum resource of MANET. Finally, fuzzy rules base was made to analyze FIADS, and comparison between FIADS and the traditional IDES was made. The simulation results show that, compared with IDES, FIADS can effectively detect the packet dropping attack action, and owns a higher detection efficiency.